Tracking red blood cells in a circular PDMS microchannel using a confocal micro-PIV system - Lima, R. (2010)
The blood flow in microcirculation is characterized mainly by the flow of red blood cells (RBCs), which may be normal or pathological. This paper presents the application of a confocal micro-P1V system lo track RBCs through a circular polydimelhysiloxane (PDMS) microchannel. This technique, consists o!’ a spinning disk confocal microscope, high speed camera and a diode-pumped solid stale (DPSS) laser combined with a single particle tracking (SPT) software (Mtracki). To show the ability of this system detailed motions o!’ individual RBCs were measured at different haematocrits (Hct): 3%, 14% and 37%. Our results show clearly that this technique can provide detailed information about micro-scale disturbance effects caused by RBCs lo the blood flow.